The planar cell polarity protein Vangl2 is involved in postsynaptic compartmentalization. (26th January 2016) - Nagaoka, Tadahiro; Kishi, Masashi
Graphical abstract: Highlights: In Vangl2-silenced neurons, the distribution of PSD-95 is rather diffused. In addition, the formed clusters of PSD-95 overlap with N-cadherin more frequently. PCP-related mechanism may underlie the postsynaptic regionalization. Abstract: The excitatory postsynaptic region of the vertebrate hippocampus is usually compartmentalized into the postsynaptic density (PSD) and N-cadherin-rich domain, which is important for synaptic adhesion. However, the molecular mechanisms underlying the compartment formation are unknown. In the present report, we show that the planar cell polarity (PCP) protein Van Gogh-like 2 (Vangl2) plays a role in this regionalization. In cultured rat hippocampal neurons that were subjected to Vangl2 expression silencing, the formed clusters of PSD-95, one of the major scaffolding proteins in PSD, tended to overlap with those of N-cadherin. Further, in the dendrites of these neurons, the immunofluorescence of PSD-95 was to some extent diffused, without a significant change in the total signal. Because Vangl2 physically interacts with both PSD-95 and N-cadherin in vivo, these results suggest that a PCP-related direct molecular mechanism underlies the horizontal polarization of the postsynaptic regions.